1990
DOI: 10.1172/jci114861
|View full text |Cite
|
Sign up to set email alerts
|

Noncoordinate regulation of alpha-1 adrenoreceptor coupling and reexpression of alpha skeletal actin in myocardial infarction-induced left ventricular failure in rats.

Abstract: To determine the effects of myocardial infarction-induced left ventricular failure on the regulation of surface alpha-1 adrenoreceptors and signal transduction, large infarcts were produced in rats and the animals killed seven days later. After the documentation of impaired left ventricular pump performance, radioligand binding studies of the alpha-1 adrenoreceptor, norepinephrine-stimulated phosphoinositol turnover, and ADP ribosylation of 41 kD substrate by pertussis toxin were examined in the hypertrophying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Possible candidates include the AT 1 angiotensin II receptor subtype and ␣ 1 -adrenergic receptors, which can be upregulated in the presence of ventricular dysfunction and failure. 45,46 We were unable to document that the p53 bands with shifted gel mobility could be further retarded by the addition of p53 antibodies in nuclear extracts from myocytes of normal and paced hearts. This may be a consequence of the level of expression of endogenous p53 in control and stressed myocytes.…”
Section: Pacing-induced Heart Failure and P53mentioning
confidence: 84%
“…Possible candidates include the AT 1 angiotensin II receptor subtype and ␣ 1 -adrenergic receptors, which can be upregulated in the presence of ventricular dysfunction and failure. 45,46 We were unable to document that the p53 bands with shifted gel mobility could be further retarded by the addition of p53 antibodies in nuclear extracts from myocytes of normal and paced hearts. This may be a consequence of the level of expression of endogenous p53 in control and stressed myocytes.…”
Section: Pacing-induced Heart Failure and P53mentioning
confidence: 84%
“…Although changes in the half-lives of ATla-R and AT2-R transcripts could not be measured in this study, the results suggested that gene transcription as well as mRNA turnover are enhanced in the infarcted myocardium. Myocardial infarction (46,47), like cardiac hypertrophy, induces the "fetal program" (induction of skeletal a-actin and atrial natriuretic factor) and stimulates expression of the TGF-/31 (48), angiotensinogen (15), and ACE genes (16), suggesting that the synthesis of cardiac Angil is increased in the infarcted heart. Angil can upregulate the expression of the atrial natriuretic factor (49), angiotensinogen (39), and TGF-f31 genes (39) in neonatal rat myocytes by means of an AT1-R mediating mechanism (39).…”
Section: Discussionmentioning
confidence: 99%
“…7 The reactive hypertrophic growth adaptation of viable myocytes was found to be accompanied by an enhanced norepinephrine-stimulated phosphoinositol turnover and upregulation of the fetal sarcomeric actin isoform.7 These findings provided a construct for the hypothesis that a1-adrenoreceptors, singularly or in concert with other growth-promoting factors, may regulate myocyte hypertrophy. On the other hand, if the a1-adrenoreceptor controls only one component of the changes in myocyte length and diameter, other surface receptors may be implicated in the modulation of myocyte growth.…”
Section: Regulation Of Angiotensin II Receptors On Ventricular Myocytmentioning
confidence: 93%